Value Analysis: Study of Application in Malaysia’s Construction Industry - Abdullah, Muhammad Ikhwan (Universiti Teknologi Petronas, 2012)
Malaysian government has realized that it is necessary to modernize the construction industry to keep in line with international practice and long term healthy growth. As a result, the use of Value Analysis as an advanced management technologies and skills was highlighted. From the previous study and interviews carried out, it was found that the participants in the construction industry lack awareness in Value Analysis. Therefore the research is carried out to study the typical Value Analysis job plan methodology, the degree of awareness and understanding of Value Analysis in construction industry, the degree of implementation and effectiveness of the Value Analysis job plan, and the drivers and obstacles in implementing Value Analysis. The study was done through qualitative methods and analyzed using average index. Then the data analysis will be carried out by using average index method. Through the study it was identified that awareness level and implementation of Value Analysis was good. However, the understanding level and effectiveness are low.